1965
DOI: 10.1152/ajplegacy.1965.209.1.105
|View full text |Cite
|
Sign up to set email alerts
|

Bulbar gustatory responses to anterior and to posterior tongue stimulation in the rat

Abstract: Amplitudes of neural responses in the nucleus of the fasciculus solitarius to stimulation of the tongue with quinine hydrochloride were analyzed using the response to NaCl as a reference standard. Three distinguishable areas were observed within the gustatory response zone of the nucleus. One area, responsive only to stimulation of the anterior region of the tongue, was at the anterolateral limit of the active zone. A second area, caudal and medial to the first, responded to both anterior and posterior tongue-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(42 citation statements)
references
References 1 publication
5
37
0
Order By: Relevance
“…The intermediate response magnitudes suggested complex interactions between different receptive fields in the rNST. An early study (Halpern and Nelson 1965) reported increased responses in rNST neurons after CT block (by local anesthesia), suggesting an inhibitory influence from the CT on rNST neurons. Moreover, CT activation by electrical stimulation selectively reduced responses to quinine in the rNST neurons but had no effect on responses to NaCl.…”
Section: Implications Of Umami Tastants or Artificial Salivamentioning
confidence: 99%
See 1 more Smart Citation
“…The intermediate response magnitudes suggested complex interactions between different receptive fields in the rNST. An early study (Halpern and Nelson 1965) reported increased responses in rNST neurons after CT block (by local anesthesia), suggesting an inhibitory influence from the CT on rNST neurons. Moreover, CT activation by electrical stimulation selectively reduced responses to quinine in the rNST neurons but had no effect on responses to NaCl.…”
Section: Implications Of Umami Tastants or Artificial Salivamentioning
confidence: 99%
“…However, recent studies have reported overlapping terminal projections from these afferent nerves (Corson et al 2012;May and Hill 2006). In studies examining the oral receptive field properties of taste-sensitive neurons in the rNST, oral receptive field configurations in the horizontal plane were associated with afferent projections along the RC axis in the rNST (Halpern and Nelson 1965;Sweazey and Smith 1987;Travers and Norgren 1995). Of individual neurons, one-third actually received convergent inputs from the different receptive fields, primarily the anterior tongue and the nasoincisor duct, which are innervated by the CT and the GSP, respectively (Travers et al 1986).…”
mentioning
confidence: 99%
“…In both species the CT projects taste information first to the rostral portion of the nucleus of the solitary tract (NTS) [96]. In rodents efferents from the NTS are then sent to the medial parabrachial nucleus.…”
Section: Taste and Sodium Appetitementioning
confidence: 99%
“…Therefore, individual rNTS neurons may integrate input from the whole tongue. In fact, electrophysiological studies have suggested convergence of inputs from areas of the oral cavity innervated by the facial and glossopharyngeal nerves onto single rNTS neurons in rat (Halpern and Nelson, 1965;Travers et al, 1986) and hamster (Sweazey and Smith, 1987). In addition, the predominantly rostrocaudally extending dendrites imply that portions of the rostral and causal NTS may be interconnected.…”
Section: Implications For the Functional Organization Of The Rntsmentioning
confidence: 99%